2015
DOI: 10.1039/c5ib00208g
|View full text |Cite
|
Sign up to set email alerts
|

Collective motion of mammalian cell cohorts in 3D

Abstract: Collective cell migration is ubiquitous in biology, from development to cancer; it occurs in complex systems comprised of heterogeneous cell types, signals and matrices, and requires large scale regulation in space and time. Understanding how cells achieve organized collective motility is crucial to addressing cellular and tissue function and disease progression. While current two-dimensional model systems recapitulate the dynamic properties of collective cell migration, quantitative three-dimensional equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…How collectively migrating cells depend on leader cells, or can self-organize, is itself an ongoing research effort [21]. This research also has potential clinical applications.…”
Section: The Role Of the Tumor Microenvironment In Cancer Cell Migrationmentioning
confidence: 99%
“…How collectively migrating cells depend on leader cells, or can self-organize, is itself an ongoing research effort [21]. This research also has potential clinical applications.…”
Section: The Role Of the Tumor Microenvironment In Cancer Cell Migrationmentioning
confidence: 99%
“…In this paper, we have implemented both free (cells are unconfined) and no-flux (reflective) boundary conditions. A similar 3D model has also been developed by Sharma et al (2015), with small but important differences in the model implementation. Crucially, we have kept the original idea by Grégoire et al (2003) to restrict interactions to nearest Voronoi neighbors.…”
Section: Extension To Three Dimensionsmentioning
confidence: 99%
“…Heterogeneity of cell migration is of great interest to cancer research, for example to identify whether a subpopulation of cells in a tumor is more invasive, and how this invasive behaviour can be modulated by drugs or microenvironmental properties. Recent studies of mammalian cell cohorts in 3D environments have used delay correlation analysis to quantify heterogeneity (Sharma et al, 2015). The authors found a range of delay distributions of different cell clusters, indicating potential evidence for heterogeneity of movement between different cell clusters (although making no direct claim as to any underlying heterogeneity of cell states themselves).…”
Section: Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of these tools has made it possible to track not only cellular motion velocity but also directional migration persistence, mean‐squared displacement (MSD), the velocity correlation, the cell‐pair separation distance, and so on. Nonetheless, more quantified variables are needed to quantify and distinguish different patterns of migration modes in both single‐cell and collective cell migration, such as transition between amoeboid and mesenchymal migration, cellular leadership in collective behavior . Additionally, not all tools are applicable in native like three‐dimensional environments.…”
Section: Introductionmentioning
confidence: 99%